1988
DOI: 10.1159/000174447
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Failure Complicating Acute Myocardial Infarction - Problems and Potential of Nonthrombolytic Therapy

Abstract: Despite recent advances, problems in the treatment of acute myocardial infarction still remain. In the earliest stages of the syndrome thrombolysis holds substantial if not absolute promise but many patients present too late for it to be effective. In these latter individuals and those in whom thrombolysis was not successful, the major mortality risk is concentrated in those with left ventricular failure. Many drugs, including diuretics, vasodilators, ACE inhibitors and positive inotropes, singly or in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Contributing factors are most likely the improvement in the prehospital care [3], the early detection and treatment of lifethreatening arrhythmias, a more aggressive treatment of pain [4] and congestive heart failure [5] in the acute phase, and the more frequent early use of ß-blockers [6] and possibly nitroglycerin [7].…”
Section: Introductionmentioning
confidence: 99%
“…Contributing factors are most likely the improvement in the prehospital care [3], the early detection and treatment of lifethreatening arrhythmias, a more aggressive treatment of pain [4] and congestive heart failure [5] in the acute phase, and the more frequent early use of ß-blockers [6] and possibly nitroglycerin [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that patients with congestive heart failure complicating acute myocardial infarction have poor prognosis [5][6][7][8][9]. Even in the thrombolytic era, left ventricular dysfunction remains the single most important predictor of mortality following acute myocardial infarction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Contributing factors are most likely the improvement in the prehospital care [3], the early detection and treatment of life-threatening arrhythmias, a more aggressive treatment of pain [4]and congestive heart failure [5]in the acute phase, and the more frequent early use of β-blockers [6]and possibly nitroglycerin [7]. …”
Section: Introductionmentioning
confidence: 99%